Assessing the feasibility and acceptability of a peer-based communication coaching model among hospital clinicians - Kathryn I. Pollak; Xiaomei Gao; Danielle Kennedy; Amal Youssef-Elgamal; Amelia Morales; Jonathan Huntington; Eliseu Chuang; Adia Ross (Elsevier, 2022)
Objective: Communication coaching shows promise for improving clinician communication yet few have assessed the feasibility of having peers coach each other. We conducted a proof-of-concept study to test the feasibility and acceptability of a peer-based communication coaching program in an inpatient setting. Methods: We trained three clinician communication coaches (two physicians and one physician assistant) and randomized half of the 27 clinicians working on the general medicine floor to receive coaching. The coaching involved shadowing and providing feedback on real-time encounters with patients. We collected data on feasibility of providing the coaching, quantitative and qualitative ratings of acceptability of the coaching both from the clinician and the coach perspective, and clinician burnout. Results: We found the peer coaching to be feasible and acceptable. Quantitative and qualitative reports support the merit of the coaching; most clinicians who received the coaching reported making changes in their communication. Clinicians in the intervention arm reported less burnout than those who did not receive the coaching. Conclusions: This proof-of-concept pilot showed that peer coaches can provide communication coaching and that clinicians and coaches viewed the coaching as acceptable and might change communication. The coaching also seems to show promise on burnout. We provide lessons learned and thoughts about how to improve the program. Innovation: Teaching clinicians to coach each other is innovative. We conducted a pilot that shows promise for feasibility, acceptability of clinicians coaching each other to communicate better, and a signal that it can help improve clinician burnout.